Internal Control Structure - Study of Business Units - Jerkku, Lasse (My University, 2008)
The purpose of the study is to examine the internal control structures of business units. The contingency control theory is congruent with the internal control literature; all organizations need control over their activities but the control structures may vary. First, the internal control structure is examined between large and medium-size business units. Second, this study compares the internal control structures of manufacturing and project units. The study is conducted in a Finnish country level organization of a multinational corporation. The research sample consists of ten business units. A survey, directed to the management of the business units, is conducted to obtain the research data. The research questionnaire is developed to provide quantitative data of the internal control structures in the business units. The non-parametric Mann-Whitney U-test is used in the statistical analysis. The results of the study found no significant difference between the internal control structures of large and medium-size business units. This concurs with findings of previous internal control literature. The Mann-Whitney U-test conducted between manufacturing and project units found also no statistical difference. Management control literature has found environmental variables, such as products and customers, to affect control structures. The study concludes that the operation of the business unit might not be precise enough contextual variable to reveal differences between business units.
Keywords: internal control structure; contingency theory; business unit; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|